Analisis Penerimaan Teknologi Kecerdasan Buatan dalam Pembelajaran Pemrograman Web: Pendekatan Model Penerimaan Teknologi - Putra, Muhammad Trio Maulana; Rochmah, Irma Nuur; Sa’adah, Nurul Laili; Sabar, Sabar; Sari, Nitta Puspita (EDUTIC, 2025)
In the rapidly evolving digital era, the application of artificial intelligence (AI) technology in education, particularly in web programming learning, presents new challenges and opportunities. This study aims to explore students' perceptions of using AI in web programming education by employing the Technology Acceptance Model (TAM) as a theoretical framework. The research method used is a quantitative approach with a survey design, involving 47 students from the Information Technology Education Study Program at Mojosari Institute of Technology. The analysis results indicate that students have a positive perception of the ease of use and usefulness of AI, as well as a strong intention to continue using this technology in their learning. Despite the challenges in implementing AI, the findings suggest that AI has significant potential to enhance the effectiveness of web programming education. This research is expected to provide insights for the development of more effective curricula and teaching strategies.